Transient stability improvement for electrical power systems based on the impedance change of a transmission system - R. V. Silva, Tatiana [UNESP]; Isoda, Lilian Y. [UNESP]; S. Tonelli-Neto, Mauro [UNESP]; A. Alves, Dilson [UNESP]; Minussi, Carlos R. [UNESP] (Hindawi, 2020)
This study presents a new preventive control model based on sensitivity analysis that aims to improve the transient stability by changing the configuration of the transmission system. By considering a list of severe contingencies for electrical power systems through security analysis, once exists instability cases in the sense of transient stability, the sensitivity analysis in this article provides the “best localization” and the respective quantification of transmission lines to correct the system's security to a desired security margin. With this preventive control strategy, one can obtain a secure configuration of the power system. Several studies present transmission reinforcement, for example, transmission line inclusion, as an efficient approach. In this study, the system will improve the stability for every short circuit fault considered, increasing the transmission capacity. This detail can be illustrated using a simple transient stability method, namely, the equal-area criterion. Considering adaptations and some simplifications, the results obtained in this work can be used for FACTS devices. The stability analysis is conducted using the security margin concept determined by the direct Lyapunov energy method; it is a support tool that aids planners and operators of electric power systems. In addition, a procedure called security margin displacement effort is presented in order to infer the numerical validity of the sensitivity model. The method is tested with a power system composed of 45 buses, 73 transmission lines, and 10 synchronous machines.
Keywords: electric power system; energy function; security margin; sensitivity analysis; transient stability; transmission system impedance change